Land Conversion and Farmer Exclusion: Land Tenure Change and Livelihoods Transformation in Sukamakmur Village, Karawang Regency - Aini, Sonia; Kurnia, Ganjar; Bachiardi, Dianto; Choibar Tridakusumah, Ahmad (Sodality: Jurnal Sosiologi Pedesaan, 2024)
The conversion of agricultural land in Karawang Regency, particularly in Sukamakmur Village, has significantly disrupted farmers' livelihoods. This study examines the socio-economic changes farmers experienced before and after exclusion from their cultivated lands. Using a qualitative case study approach, data were gathered through interviews with ten informants across different land tenure classes, alongside insights from government officials and stakeholders. The findings reveal that policies favoring industrial development, speculative land sales, and inadequate irrigation infrastructure have driven widespread land conversion. These forces compelled farmers to sell their land, resulting in shifts in land ownership, reduced incomes, and altered livelihoods. Many displaced farmers became tenants, sharecroppers, or laborers, while others left agriculture entirely. Low education and skill deficits further hindered their ability to transition to industrial jobs, exacerbating inequality and poverty. This study highlights the systemic marginalization of farmers and calls for policies to protect their rights and promote equitable rural development.